2017
DOI: 10.3389/fphys.2017.01093
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Soccer Training on Anthropometry, Body Composition, and Physical Fitness during a Soccer Season in Female Elite Young Athletes: A Prospective Cohort Study

Abstract: The objectives of this study were to (i) describe soccer training (e.g., volume, types), anthropometry, body composition, and physical fitness and (ii) compute associations between soccer training data and relative changes of anthropometry, body composition, and physical fitness during a soccer season in female elite young athletes. Seasonal training (i.e., day-to-day training volume/types) as well as variations in anthropometry (e.g., body height/mass), body composition (e.g., lean body/fat mass), and physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
1
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 64 publications
5
39
1
9
Order By: Relevance
“…The present study is consistent with the results of Shafabakhsh et al [21], but inconsistent with the findings of Lesinski and colleagues [22]. Shafabakhsh et al reported that cardiorespiratory endurance, flexibility, muscular endurance, and raw power have significantly improved in male students [21].…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The present study is consistent with the results of Shafabakhsh et al [21], but inconsistent with the findings of Lesinski and colleagues [22]. Shafabakhsh et al reported that cardiorespiratory endurance, flexibility, muscular endurance, and raw power have significantly improved in male students [21].…”
Section: Discussionsupporting
confidence: 70%
“…There was no significant change in muscular strength/endurance, speed, and directional change in speed. The muscle strength of thigh muscle was reduced [22]. The selected football exercises had significantly affected participants' agility.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…La velocidad y la potencia son características físicas de gran importancia en el fútbol; el desarrollo de la fuerza explosiva de miembros inferiores es indispensable para alcanzar la capacidad de salto deseada (13) . En el deporte la capacidad de salto (CS) es evaluada normalmente a través del "test de Bosco", utilizando los diferentes tipos de salto como el salto sin impulso (SJ), salto contra -movimiento (CMJ), salto Abalakov (ABLKJ) y salto máximo (MJ) (2,14) .…”
Section: Resultsunclassified
“…El fútbol femenino es cada día más popular entre las mujeres y el desarrollo de cualidades físicas específicas se beneficia en forma notable cuando existe una adecuada composición corporal (1) . Además, la restricción calórica acompañada de ejercicio de mediana intensidad causa mejoras importantes en la composición corporal (2) .…”
Section: Introductionunclassified